Popular participation in the preservation of the Municipal Theater of São João da Boa Vista - Dragão Jeronimo, Luis Pedro (Em Perspectiva, 2024)
The Municipal Theater of São João da Boa Vista, built in 1914, is one of the main cultural stages of the region in which it operates. Threatened with demolition, its current existence was only made possible by the involvement of the community in its preservation. In this regard, between the early 1980s and the early 2000s, we see a joint effort by citizens and public authorities to restore and conserve that building that marked sanjoanense cultural life. This article aims to examine the individual and collective actions of community members who, by putting pressure on the public authorities and making themselves heard, ended up preserving not only a building, but part of their stories, memories and identities.